TINJAUAN PENGATURAN PENGEMBALIAN KEUNTUNGAN TIDAK SAH DAN DANA KOMPENSASI KERUGIAN INVESTOR DI BIDANG PASAR MODAL INDONESIA - Afilya Hunaifa; Dona Budi Kharisma (Jurnal Privat Law, 2026)
This article examines the regulation of disgorgement in Indonesia. This research is prescriptive normative legal research with statutory approach. The data used were primary, secondary, and tertiary legal materials. Data collection techniques carried out by literature study or document study with deductive syllogism legal material analysis techniques. The results of the research and discussion show that disgorgement is important in the effectiveness of law enforcement by punisihing criminals a direct punishment, it can reduce crime in the capital market itself.